WE7.13 Blunt Hepatic Trauma at a Major Trauma Centre in the North West of England between 2000 and 2020. (9th August 2022) - Reader, Harriet; Lunevicius, Raimundas
Abstract: Background: Our institution became a Major Trauma Centre (MTC) in 2012, currently serving a population of 2.3 million. This study aims to evaluate the trends in blunt hepatic trauma (BHT) and the changes in management strategy over time (pre- and post- MTC era). Methods: This was a single-centre, retrospective cohort study. Data were obtained from the Trauma Audit and Research Network (TARN) database across a 20-year period (2000–2020). Results: 209 patients presented with BHT: 31 in 2000–2011 and 178 in 2012–2020. The median age was 35.6 and M:F ratio was 2.8:1. Road traffic accidents (RTAs) were the most common mechanism (n=124, 59.3%), followed by fall from height (n=44, 21.1%). Patients had a median ISS of 25 (range 4–75). 109 patients were managed conservatively (52.5%), with 10 of these patients having angioembolisation. Although 100 patients (47.8%) underwent operative management, only 7 patients underwent liver surgeries such as liver laceration repair (n=7, 3.3%) or resection (n=2, 1%). Mortality rate was 13.8% (n=44) in the conservative group and 21% in the operative group. The overall mortality was 16.7% (n=35). The subgroups analyses revealed no significant difference in mortality for patients managed non-operatively. Conclusions: BHT patients frequently present as a polytrauma. Only 3.3% required a laparotomy and intervention to the liver parenchyma. The establishment of the MTC was associated with a significant increase in BHT presentations. The proportion of conservatively managed patients was similar pre- and post-MTC eras. The mortality rates were not significantly different.